Al-Zahrawi method on inflammatory swellings and tumours surgery - Bilal, Sara Mohammed Osman Saleh; Kabbashi, Nassereldeen Ahmed (IIUM Press, 2011)
The objective ofthis chapter is to list the contribution of AI-Zahrawi in the surgery of swellings and tumours. This chapter explores AI- Zahrawi as a surgeon in the field of inflammatory swellings and tumours. He was known as the most notable Muslim surgeon during the Islamic civilization. His name is Abu-AI-Qasim Khalaf Ibn'Abbas AI-Zahrawi known as Abulcasis, Bucasis or Alzahravius. In 930 A.D., he was born in AI-Zahra, a suburb of Cordova. He attended the University of Cordova which had been established for one and a half centuries. AI-Zahrawi as a physician was appointed as the Court-Physician of King Abdel-Rahman III (Amr SS, 2007, pp. 220-1). He spent a productive life in practicing medicine, especially in surgery and medical writings. He wrote mainly four books. One of them is "AI_Tastif Liman Ajiz'an Al-Ta'lif' which is the best medieval surgical encyclopaedia